Awareness and use of information communication technologies by farmers in Oyo State, Nigeria (2012)
Due to inadequate personnel, information communication technologies (ICTs) have become an attractive option for delivery of extension information. This study examined awareness and use of ICTs by farmers in Oyo State, Nigeria. A total of 192 farmers were interviewed. Results indicate that most farmers had no formal education and small farm holdings. Awareness of older ICTs like radio and television was more prevalent among farmers as compared with newer ICTs such as internet and cable television. However, use of modern ICTs like mobile phones and cable television was greater than that for older technologies such as fax machines. Farmers were constrained in ICT use by prohibitive cost and service failure. The Nigerian government should encourage a liberal policy for affordable prices for modern ICT products, especially mobile telephones.